Kegiatan Marketing Public Relations dalam Mempertahankan Citra Perusahaan - Dikhorir Afnan; Fathurrohman Fathurrohman (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2020)
Abstract. Common to many organizations, the complexity of the problems faced by organizations requires that public communication activities or mass communication run smoothly without information obstruction. In the context of today's global and massive culture, the most common challenge faced by the public relations division is maintaining communication between the company and its audience so that it can continue to be conducive. Therefore the communication system needs to be built properly in order to maintain harmony between the company and the audience. In this study the authors used a qualitative methodological approach. This research can also be referred to as descriptive research, which is research that prioritizes narration and pictures as illustrations of what is happening in the field. Public relations activities are a combination of arts and other social sciences that can detect symptoms that are happening and what will happen in the future. The conclusion of this research is that marketing public relations (MPR) must maximize services by, among other things, fostering and maintaining the company's image or products and services, both in terms of the quantity and quality of services provided to consumers. Keywords: Marketing Public Relations, Mass Communication, Public Opinion, Audience, Corporate Image.